Decreased exercise capacity in young athletes using self-adapted mouthguards - Lässing, J.; Falz, R., Schulze, A.; Pökel, C.; Vondran, M.; Schröter, T.; Borger, M. A.; Busse, M. (European Journal of Applied Physiology, 2021)
Purpose: There is evidence of both the preventive effects and poor acceptance of mouthguards. There are various effects on performance depending on the type of mouthguard model. Hemodynamic responses to wearing a mouthguard have not been described. The aim of this study was to investigate the effects of self-adapted mouthguards with breathing channels (SAMGvent). Methods: In this randomized crossover study, 17 healthy, active subjects (age 25.12 ± 2.19 years) underwent body plethysmography and performed two incremental exertion tests wearing a (SAMGvent) and not wearing (CON) a mouthguard. Blood lactate, spirometrics, and thoracic impedance were measured during these maximum exercise tests. Results: The mean values using a SAMGvent revealed significantly greater airway resistance compared to CON (0.53 ± 0.16 kPa·L-1 vs. 0.35 ± 0.10 kPa·L-1, respectively; p = < 0.01). At maximum load, ventilation with SAMGvent was less than CON (118.4 ± 28.17 L min-1 vs. 128.2 ± 32.16 L min-1, respectively; p = < 0.01). At submaximal loads, blood lactate responses with SAMGvent were higher than CON (8.68 ± 2.20 mmol·L-1 vs. 7.89 ± 1.65 mmol·L-1, respectively; p < 0.01). Maximum performance with a SAMGvent was 265.9 ± 59.9 W, and without a mouthguard was 272.9 ± 60.8 W (p < 0.01). Maximum stroke volume was higher using a SAMGvent than without using a mouthguard (138.4 ± 29.9 mL vs. 130.2 ± 21.2 mL, respectively; p < 0.01). Conclusion: Use of a self-adapted mouthguard led to increased metabolic effort and a significant reduction in ventilation parameters. Unchanged oxygen uptake may be the result of cardiopulmonary compensation and increased breathing efforts, which slightly affects performance. These results and the obvious preventive effects of mouthguards support their use in sports.